MEDICAL DOCTORS’ PROCEDURAL SKILL PERFORMANCE AND ATTITUDE TOWARD ULTRASOUND-GUIDED PERICARDIOCENTESIS MODEL - Linn Htet Aung; Thasaneeya Ratanaroutai Nopparatjamjomras; Suchai Nopparatjamjomras (Yayasan Aliansi Cendekiawan Indonesia Thailand (Indonesian Scholars' Alliance), 2017)
Background: Pericardiocentesis is regarded as a procedure that has the potential for saving lives. This procedure is indicated in patients with the diagnosis of cardiac tamponade and hemodynamic shock and should be done urgently to such cases. There would be severe complications if this procedure is not performed properly and skillfully. In this study, a newly developed ultrasound-guided pericardiocentesis model was used for training procedural skill with the aim to allow undergraduate medical students experience the procedure with the cheap and easily built model. Aims: The objectives of the study were to develop ultrasound-guided pericardiocentesis model, to determine its usefulness for training the procedural skill, and to evaluate the medical doctors’ attitude toward training with the model. Methods: This pilot study was conducted to try out the model with medical doctors. The practical workshop plan for the trying out the model was developed. Video recording during the procedure, the questionnaire, and the semi-structured interview were conducted after the participants performed the procedure to assess their perception regarding with the efficacy and usefulness of the model. Results: According to results, the participants could recognize the free fluid, pericardium, and heart of the model in ultrasound screen (4.2 ± 0.45, 4.6 ± 0.55, and 4.4 ± 0.55 respectively). The model was suitable for training ultrasound-guided pericardiocentesis (4.4 ± 0.55). The model was perceived to be good and useful for training ultrasound-guided pericardiocentesis. The participants also wanted to use the model for teaching the procedural skill to medical students before performing with the real patients. Conclusions: The model was considered to be useful and appropriate for training the procedural skill. Therefore, the model could be used as the effective training tool for training ultrasound-guided pericardiocentesis.